A Model for Analysis of the Porous Nickel Electrode Polarization in the Molten Carbonate Electrolysis Cell. Issue 8 (1st January 2017) - Hu, Lan; Ekström, Henrik; Lindbergh, Göran; Lagergren, Carina
Abstract : It is important to know the electrode kinetics of hydrogen production as well as to understand the effect of the mass transport in the gas phase for the analysis of the molten carbonate electrolysis cell (MCEC). A one-dimensional model based on the Maxwell-Stefan diffusion equations was applied to predict the mass transfer behavior in gas phase of the porous nickel electrode in the MCEC, combined with equations describing the current distribution in the electrolyte phase. The model gave a fair match to the experimental polarization data of the Ni electrode for varied inlet gas compositions of H2 O, CO2 and H2 between 10 and 40%. The model was also deployed to evaluate the effect of the water-gas shift reaction (WGSR). The fitted kinetic coefficients and electrode porosity differed in the case when including the WGSR compared to when not including the WGSR. In both cases the model was able to well describe the porous nickel electrode behavior in the molten carbonate electrolysis cell.